Multilingual Education in Islamic Boarding Schools: Planning, Implementation and Institutional Policy/ Pendidikan Multi Bahasa Di Pesantren: Perencanaan, Implementasi Dan Kebijakan Kelembagaan - Nasir, Amin; Juhri, Juhri; Karim, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study investigates cases of language 'policing' as educational language policies and how these are represented across different policy levels. Focusing on Indonesian schools and using discursive approaches to language policy as a theoretical framework, I critically examine institutions' motivations and justifications for designing and implementing policies whereby non-standardized forms are 'banned' and how these are reported in metalinguistic discourse. Drawing on a range of data, including media discourse, policy documents, teacher interviews, and linguistic landscapes, I textually trace how educational language policies (re)produce prescriptive and linguist ideologies, often using metaphors of crime and often using language as a proxy for social factors such as academic achievement, employability, and standards. Overall, micro- and meso-level language policies are a partial product of linguistic conservatism in current macro-level educational policy. (Language policy, language policing, schools, language ideologies).